Current Issues and Challenges in the Dairy Industry - Ibrahim, Salam A.; Zimmerman, Tahl; Gyawali, Rabin; Ibrahim, Salam A.; Zimmerman, Tahl; Gyawali, Rabin (IntechOpen, 2020)
The dairy industry has faced several challenges that have impacted dairy food quality and consumer acceptability. This book presents a different approach to address current issues and challenges facing the dairy industry. The book consists of seven chapters dealing with dairy processing, current issues related to consumers, and probiotic characteristics. We hope that this first edition can build interest among other scientists to join our future effort to write a more comprehensive book on this topic.
English
Keywords: Agriculture & related industries; Agriculture & related industries